2023
DOI: 10.1002/agt2.330
|View full text |Cite
|
Sign up to set email alerts
|

An overview on AIEgen‐decorated porphyrins: Current status and applications

Abstract: One of the major obstacles of porphyrins is the aggregation-caused quenching (ACQ) of photoluminescence due to the strong intermolecular π-π interaction of the planar porphyrin core in the solid state. However, ACQ leads to the nonradiative deactivation of the photoexcited states which results in short-lived charge-separated states and thus low photoluminescence and singlet quantum yields. This phenomenon would limit the utilization of porphyrins in near-infrared fluorescent bioimaging, photodynamic therapy, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Noteworthily, the absorption profile of TPE‐ZnPF is highly red‐shifted and broadened in THF/water (H 2 O) mixture solution compared to that in THF solution, implying the formation of J ‐type aggregates in THF/H 2 O. [ 15 ] In the case of Ph‐ZnPF, the absorption profile is slightly red‐shifted and broadened in THF/H 2 O in comparison to that in THF. Obviously, TPE‐ZnPF aggregates cover a much broader absorption spectrum from 290 to 920 nm than Ph‐ZnPF aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthily, the absorption profile of TPE‐ZnPF is highly red‐shifted and broadened in THF/water (H 2 O) mixture solution compared to that in THF solution, implying the formation of J ‐type aggregates in THF/H 2 O. [ 15 ] In the case of Ph‐ZnPF, the absorption profile is slightly red‐shifted and broadened in THF/H 2 O in comparison to that in THF. Obviously, TPE‐ZnPF aggregates cover a much broader absorption spectrum from 290 to 920 nm than Ph‐ZnPF aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…[1] However, most porphyrins exhibit aggregation-caused quenching (ACQ) of photoluminescence in the solid state due to the strong π-π stacking of planar porphyrin moieties. [14,15] This tendency activates the nonradiative decay channels which further shorten the electron lifetimes (τ PL ) of photoexcited states and subsequently low photoluminescence quantum yields (Φ PL ) and therefore inferior PHE performance of porphyrin-based photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Al porphyrin was widely studied in the ROCOP of epoxide/cyclic anhydride. The porphyrin complexes featured with large π-conjugated systems , could promote the intramolecular multiple interactions between Mn and Al centers for better catalytic performance. Collectively, a series of tandem polymeric Mn–Al porphyrin catalysts were designed, as shown in Figure a. Oxidant was also an important part of the ISECOP system.…”
Section: Resultsmentioning
confidence: 99%
“…21−23 The poor stability of water-soluble porphyrins and the aggregation-caused quenching (ACQ) effect result in low ECL emission efficiency, which limits their application as emitters in the field of ECL. 24 ACQ is a phenomenon prevalent in conventional fluorescent polymers. Fluorescent substances exhibit high fluorescence at low concentrations and partial or complete bursting at high concentrations or in the aggregated state, which is defined as the ACQ effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, the excellent properties of porphyrins in photovoltaics have extended the application of some porphyrin-based materials in photocatalysis, energy transfer, and sensing . In addition, the broad potential, rigid structure, and abundant coordination chemistry have also made them of widespread interest as ECL luminophores. , However, among the few studies reported on the application of porphyrins in ECL systems, most of them are only soluble in organic solvents. The poor stability of water-soluble porphyrins and the aggregation-caused quenching (ACQ) effect result in low ECL emission efficiency, which limits their application as emitters in the field of ECL . ACQ is a phenomenon prevalent in conventional fluorescent polymers.…”
Section: Introductionmentioning
confidence: 99%